Determinants of small and medium-sized enterprises performance: The evidence from Vietnam - Nguyen Kim Quoc Trung (Cogent Business & Management, 2021)
This paper estimates the factors affecting Vietnamese small and medium-sized enterprises (SMEs) listed on the Hanoi Stock Exchange and the Chi Minh City Stock Exchange between 2009 and 2019. The author adopts a quantitative method (the "Generalized Method of Moments"-GMM) to investigate six statistically significant variables positively affecting SMEs' performance at 5%. These variables include the profitability lag, firm size, leverage ratio, revenue growth, gross domestic product growth, and the quality of national governance. One of the significant contributions of this study to the literature is to consider the leverage ratio as a tool to improve SMEs' performance, and national governance quality is a mechanism to enhance SMEs' efficiency.
Keywords: L25; L31; O12; P47; 650; small and medium-sized enterprises (SMEs); performance; leverage; national governance quality; Generalized Method of Moments-GMM; Vietnam